PENGARUH KESULITAN KEUANGAN, FINANCIAL LEVERAGE DAN PENGHINDARAN PAJAK TERHADAP KONSERVATISME AKUNTANSI (Studi Empiris Pada Perusahaan Manufaktur di Bursa Efek Indonesia Tahun 2011-2014) - Ostari, Vina; Anisma, Yuneita; Rofika, Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of financial distress, financial leverage and tax evoidance against the conservatism of accounting in companies listed on the Stock Exchange in 2011-2014. selecting the sample in this study using purposive sampling method in which a population of 149 selected according to criteria of a sample of 21 companies selected. Data analysis tool used is multiple regression. The results of this study indicate that financial difficulties negatively affect accounting conservatism with a significance value of 0659, financial leverage positive effect on accounting conservatism with significant value of 0001, tax evasion positive effect on accounting conservatism with a significance value of 0.003. sigifikan value in this study was ≤ 0:05. the coefficient of determination in this study was 0.301 indicating that 30.1% of the variation in accounting conservatism terjaadi affected by financial difficulties, financial leverage and tax evasion. Its residual 69.9% influenced by other variables not included in this study.Keywords:Financial Difficulties, Financial Leverage, Tax Evasion, and Accounting Conservatism